1991
DOI: 10.1210/jcem-72-5-976
|View full text |Cite
|
Sign up to set email alerts
|

A Prepubertal Surge of Thyrotropin Precedes an Increase in Thyroxine and 3,5,3′-Triiodothyronine in Normal Children*

Abstract: The variations in plasma levels of TSH, T4, T3, and rT3, during the pubertal period, were studied in 647 school students from the urban area of Santiago in Chile (47% males and 53% females) with ages ranging between 7.5 and 15 yr. The subjects were grouped by age in consecutive intervals of 6 months each, and pubertal development was determined in every subject. TSH showed a significant increase, reaching a peak in the 9- to 9.5-yr interval. The same was found for T3 and T4, which reached a peak by 10 and 11 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Corcoran and colleagues (27) reported that there was a peripubertal nadir in circulating levels of thyroid hormones in children, although it occurred 2 years later in boys than in girls. In another crosssectional study in children in which data from boys and girls were combined, there was a transient increase in thyrotropin secretion and a resultant rise in T4 and tri-iodothyronine (T3) that preceded clinical pubertal changes (28). In a small longitudinal study (39 children, ranging in age from 10 to 15 years), there were significant fluctuations in both total and free T3 and T4 in association with pubertal stages of development (29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corcoran and colleagues (27) reported that there was a peripubertal nadir in circulating levels of thyroid hormones in children, although it occurred 2 years later in boys than in girls. In another crosssectional study in children in which data from boys and girls were combined, there was a transient increase in thyrotropin secretion and a resultant rise in T4 and tri-iodothyronine (T3) that preceded clinical pubertal changes (28). In a small longitudinal study (39 children, ranging in age from 10 to 15 years), there were significant fluctuations in both total and free T3 and T4 in association with pubertal stages of development (29).…”
Section: Introductionmentioning
confidence: 99%
“…In a small longitudinal study (39 children, ranging in age from 10 to 15 years), there were significant fluctuations in both total and free T3 and T4 in association with pubertal stages of development (29). It has been suggested that these changes in thyroid hormone may play a role in the onset or evolution of puberty in children, and may serve as an effective adaptive mechanism for a period of rapid growth and increased energy requirements (28,29). One of the objectives of the current longitudinal study was to examine in greater detail the relationship between thyroid status and critical peripubertal events in a non-human primate model (male rhesus monkey).…”
Section: Introductionmentioning
confidence: 99%
“…A prepubertal surge of TSH between 9.0 and 9.5 yr, followed by a transient increase in circulating thyroid hormones (T 4 and T 3 ), in addition to enhanced peripheral conversion of T 4 to T 3 , may account for this adaptation (1). Adaptations of the hypothalamo-pituitary-thyroid gland axis in response to the increased energy expenditure have been suggested.…”
mentioning
confidence: 99%
“…(8) reported that circulating thyroid hormone levels reached a nadir in peripubertal boys and girls whereas Michaud et al . (9) reported a transient increase in thyroxine (T 4 ), triiodothyronine and thyroid‐stimulating hormone (TSH) levels (combined data for boys and girls) that preceded development of clinical signs of puberty. In the male rhesus monkey, we previously reported that there was a transient increase in serum T 4 levels in conjunction with pubertal enlargement of the testes (10).…”
mentioning
confidence: 99%
“…Although there is general agreement that circulating thyroid hormone levels decrease with age in children (6,7), it is unclear whether there are significant fluctuations in thyroid hormone levels in association with the onset of puberty. Corcoran et al (8) reported that circulating thyroid hormone levels reached a nadir in peripubertal boys and girls whereas Michaud et al (9) reported a transient increase in thyroxine (T 4 ), triiodothyronine and thyroidstimulating hormone (TSH) levels (combined data for boys and girls) that preceded development of clinical signs of puberty. In the male rhesus monkey, we previously reported that there was a transient increase in serum T 4 levels in conjunction with pubertal enlargement of the testes (10).…”
mentioning
confidence: 99%